DINAMIKA INTERNATIONAL TRIPARTITE RUBBER COUNCIL (ITRC) INDONESIA-MALAYSIA-THAILAND GROWTH TRIANGLE DALAM EKSPOR KARET ALAM PERIODE 2012-2017 - Siti Gessawati, - (2018)
This study discusses the dynamics of ITRC (International Tripartite Rubber Council) in the export of natural rubber period 2012-2017. Indonesia-Malaysia- Thailand is the world's largest producer of natural rubber, almost 80% of natural rubber consumption produced by the three countries ITRC. With abundant natural resource reserves, ITRC is the largest exporter and has a large international market in natural rubber commodities. So far, ITRC's natural rubber exports have been in the form of SIR 20-SMR 20-STR 20 (Standard Indonesia Rubber-Standard Malaysia Rubber-Standard Thai Rubber). In 2012 to 2016 ITRC experienced a decline in export prices of natural rubber. This makes the three countries ITRC issued a policy that is by limiting the export volume of natural rubber. This is the question of "How is the dynamics of Indonesia's cooperation in ITRC 2012- 2017?". To answer this question the researcher uses a framework that is related to one another, namely international trade, national interest, sub-regional cooperation, and IMT-GT concept. The research method used descriptive qualitative method which emphasizes the information extracting and ITRC data related to price stability of natural rubber export in global market. The results of this study explain that ITRC especially Indonesia has made efforts to increase the price of natural rubber exports in international trade